A práxis reflexiva das relações públicas na sociedade midiatizada: mediação estratégica comunicacional nos blogs corporativos - Lasta, Elisangela (2015)
The context of mediated society moves the praxis of public relations with the continuous articulation of communication strategies and mobilizes the traditional dynamics of relations and ties of organizations and publics. This may be related, theoretically and empirically, to the reflective practice of public relations; that is, to know how to "say/publicize", sustained in the ethics proposal (legitimacy), politics (relation) and aesthetics (communication processes) in the doing/being/representing non-mediatic institutions through the digital medium, here represented by the corporate blog. Bearing these considerations in mind, we construct the problem of this thesis: how to understand the reflexive practice of public relations in the context of mediated society through the use/ownership of corporate blogs as a strategic communicational mediation among multiple social actors? The overall goal is to understand the reflexive practice of public relations in the mediated society and its relationship with communication strategies. The specific objectives should be considered as: developing a methodology for the study of corporate blog as a possibility of communication strategic mediation; to identify relations and/or links established in social networks built through contextual links referring to others, among the actors of the non-mediatic institutions, considering corporate blogs and other multiple social actors; and to analyze the dynamics of communication strategies among the actors of the non-mediatic institutions of the field of study, considering their corporate blogs and other multiple social actors. This thesis is based on the empirical research in communication, considering the close relationship between the theoretical and the empirical, and operated by a theoretical and methodological device that concerns the relational level that is held to describe the actor's agency with the medium through the hidden and non-participatory observation method (JOHNSON, 2010) constructed with the Excel software; the binding level, which has assembling this logic considering the structure and the medium's own codes, by the method of structural analysis of social networks (LEMIEUX; QUIMET, 2004) built with the NodeXL software; and cognitive-critical level, which held the comparative analysis, through the analysis of statements present in the discourse (PERUZZOLO, 2004) built with the Word software, which led to the intersection of these three analyzes. This route allowed the conclusion that doing/being/representing the Actors of Non-Media Institutions of the Field of Study occurred through relationships and bonds with actors of five macro-areas, mostly in single interrelations, with different actors. These relationships and bonds were operated through communication strategies involved in the protocol social (relation) - technical (medium) - discursive (communication processes), which resulted on the negotiation of meanings of the interlocutors. However, it was also possible to notice that the control over the enunciation remains under the figure of a pedagogical discourse enunciator. The reflective practice of public relations in these circumstances implies in knowing how to say/publicize not only about the non-mediatic institutions themselves, but also about the other, with the other and through the other. The results suggest the constant reflection on the emergence of other ways of perceiving, experiencing and getting to know the praxis of public relations.